Lean Education Model (LEM) Based on Industrial Engineering Approach - Waghodekar, P. H. (Journal of Engineering Education Transformations, 2011)
This paper presents that through education and training, Human Capital can be generated fetching a country’s socio-economic prosperity. The paper argues that education sector, being a service industry, needs to imbibe some business models like Business Navigator Method, Virtual Interactive Business Environment, Process Management and Performance Management, etc. Applications of IE approaches like work simplification, standardization, lean philosophy, JIT, TPM, etc., have been proving extremely rewarding in promoting effectiveness, efficiency and economics of manufacturing world. The paper, therefore, deliberates as to how and which IE approaches are to be deployed to education sector, especially tertiary, so that the out turn of education would be of quality at a lower cost with delivery on time. Few areas are scanned for this purpose, bringing out the benefits of IE approaches applied to education sector. To be globally competitive, IE approaches are shown to be yielding desirable results. The paper, it is believed, will be of interest to all concerned.